EFEKTIVITAS SISKOHAT PADA PENDAFATARAN DAN PEMBATALAN HAJI DI KANTOR KEMENTERIAN AGAMA KABUPATEN LAMPUNG TIMUR - Ida Astri Oktaviani (Institut Agama Islam Negeri Metro, 2021)
The purpose of the research was to determine the effectiveness of the Integrated Hajj Information and Computerized System (SISKOHAT) in organizing hajj at the Ministry of Religion, East Lampung Regency, especially in the registration and cancellation of hajj. This research is a descriptive qualitative research. Data collection techniques used are in-depth interviews and documentation. The data analysis carried out by the researcher was carried out in several stages, namely: data reduction, data display and conclusions. The results of the research show that the Integrated Hajj Information and Computerization System (SISKOHAT) used by the PHU section at the Ministry of Religion Office of East Lampung Regency is very effective in improving the performance of Hajj implementation, especially Hajj registration and cancellation. This was tested with SISKOHAT components at the Office of the Ministry of Religion of East Lampung Regency in the form of software and hardware that had good quality. The achievement of SISKOHAT effectiveness can also be tested with indicators that have been met, namely the quality of systems and information, usage, user satisfaction, individual impact and perceived organizational impact.